Association between magnetic resonance imaging characteristics and pathological findings in entire posterior cruciate ligament with mucoid degeneration. Issue 3 (March 2022) - Sasaki, Ryo; Nagashima, Masaki; Takeshima, Kenichiro; Otani, Toshiro; Okada, Yoshifumi; Aida, Shinsuke; Ishii, Ken
Magnetic resonance imaging (MRI) findings of a tram-track appearance and celery stalk appearance in mucoid degeneration of the cruciate ligament are valuable; however, their pathological basis is unclear. Because these appearances are generally seen throughout the entire ligament, the association between MRI findings and pathological findings must be verified in specimens of the whole degenerated ligament, including the ligamentous attachments to bone. We herein report two cases of mucoid degeneration of the posterior cruciate ligament with osteoarthritis of the knee requiring total knee arthroplasty. The entire degenerated ligament, including the ligamentous attachments to bone, was removed and pathologically evaluated. On pathological examination, the central portion of the lesion showed typical mucoid degeneration, whereas the marginal and adherent portions showed normal ligament tissue, consistent with a tram-track appearance on T2-weighted MRI. The fibrous normal ligament tissues in the longitudinal direction in regions of mucoid degeneration were consistent with a celery stalk appearance on T2-weighted MRI. No mucoid degeneration was found in the attachment area. The tram-track appearance and celery stalk appearance of mucoid degeneration on MRI can be explained by the pathological findings.